The Contingency Theory of Managerial Accounting. - Hayes, David C. (The Accounting Review, 1977)
Abstract Working mainly from the literature of modern organization theory, it was possible to develop a model of organizational performance for internal subunits. The model hypothesizes three major contingencies which affect subunit performance: (1) factors internal to the subunit (internal factors); (2) interrelationships with other subunits (interdependency factors); and (3) interactions external to the firm (environmental factors). The contingencies operate differentially across organizational subunits. Three propositions derived from the model were examined empirically in a field study of large manufacturing organizations. Strong support for two of the propositions was found, along with indications of support for the third, by using the analytical methodology of path analysis. The final section of the paper explores the implications of the study approach and results for managerial accounting theory and practice.